Characteristics of HIV-related Stigma Among Health Facility Staff in Shenzhen, China - Wang, Wei; Wang, Liling; Wang, Jun; Zhu, Naling; Luo, Yali; Tang, Weiping; Qiao, Yaping (Current HIV Research, 2021)
Background: HIV-related stigma poses a crucial barrier to HIV therapy and prevention worldwide. Stigma taking place in healthcare settings has also been a global challenge for years. Objective: To measure HIV-related stigma among health care facilities in Baoan, Shenzhen and to take decision regarding stigma-reduction intervention. Methods: We conducted a cross-sectional survey in Shenzhen Baoan Women's and Children's Hospital, China in February 2019. We collected data on HIV-related stigma from 207 hospital staff randomly selected for an anonymous survey online by a standardized questionnaire. We analyzed the influence factors on HIV-related stigma taking place in health facilities using the statistical method. Results: The percentages of worry expressed when touching clothing, dressing wound, and drawing blood for PLWH were 60.9%, 84.5%, and 82.6%, respectively. 76.3% of respondents reported at least one form of extra precautions taken during service provision to PLWH. Younger hospital employees with less working experience were more likely concerned about occupation risk of HIV infection (P<0.05). Single workers with lower education and no experience of training on HIV-related stigma were prone to discriminatory opinions against PLWH (P<0.05). Conclusion: HIV-related stigma in health facilities remains a significant challenge, and evidence- based interventions at both systematic and individual levels are needed for improvements.
Keywords: stigma